Adult Patient Care Plan: Management of the Febrile Neutropenic Cancer Patient on an Outpatient Basis - Coleman Rotstein; Eric J Bow; The Febrile Neutropenia Care Plan Working Group (Canadian Journal of Infectious Diseases)
Invasive infection may complicate the course of neutropenic cancer patients receiving intensive chemotherapy. The rate of complications is related to prognostic factors including the underlying malignant diagnosis, the state of responsiveness of the underlying disease to treatment, the dose-intensity of the cytotoxic therapy, the duration of neutropenia, the performance status of the patient and comorbid conditions. The pathogens involved are usually the patients’ endogenous microflora, and the sites of infection are those anatomic sites colonized with the endogenous microflora. The approach to the febrile neutropenic episode requires a sequence of steps including the recognition of the febrile state (oral temperature higher than 38°C), the depth and duration of the neutropenia (absolute neutrophil count less than 0.5×109/L), the identification of a clinical focus of infection and a potential pathogen, the administration of empirical antibacterial therapy, and finally, an assessment of the outcome. Management decisions about whether to treat with oral or parenteral antibacterial agents, with a combination or single agent therapy, or as an inpatient or an outpatient can be based on an assessments of risks of the severity of the patient’s comorbid conditions and the patient’s risk of developing medical complications that would require inpatient management. The duration of antimicrobial treatment depends on the recovery from the state of neutropenia and the origin of the infectious process.